Central Venous Pressure (CVP) Reduction Associated With Higher Cardiac Output (CO) Favors Good Prognosis of Circulatory Shock: A Single-Center, Retrospective Cohort Study - Su, Longxiang; Pan, Pan; Li, Dongkai; Zhang, Qing; Zhou, Xiang; Long, Yun; Wang, Xiaoting; Liu, Dawei (Frontiers in Medicine, 2019)
Background: The Frank-Starling curve is the basis of hemodynamics. Changes in cardiac output (CO) caused by central venous pressure (CVP) are the most important concerns in the treatment of critically ill patients. Objectives: To explore the use of CVP and its relevant mechanisms with respect to CO in the clinic. Methods: A total of 134 patients with circulatory shock were retrospectively included and analyzed. Hemodynamic data were recorded and analyzed at PICCO initiation and 24 h after PICCO. Data regarding 28-day mortality and renal function were also collected. Results: The patients were divided into a CVP↑+ CO↑ group (n = 23), a CVP↑+ CO↓ group (n = 29), a CVP↓+ CO↑ group (n = 44), and a CVP↓+ CO↓ group (n = 38) based on values at PICCO initiation and 24 h after PICCO. Post- hoc tests showed that the CVP↓+ CO↑ group had a higher 28-day survival than the other groups [log-rank (Mantel-Cox) = 8.758, 95%, CI, 20.112–23.499, P = 0.033]. In terms of hemodynamic characteristics, the CVP↓+ CO↑ group had a lower cardiac function index (CFI) (4.1 ± 1.4/min) and higher extravascular lung water index (EVLWI) (11.0 ± 4.7 ml/kg) at PICCO initiation. This group used more cardiotonic drugs (77.3%, P < 0.001) and had a negative fluid balance (−780.4 ± 1720.6 ml/24 h, P = 0.018) 24 h after PICCO than the other three groups. Cardiotonic drug use and dehydration treatment were associated with increased CFI (from 4.1 ± 1.4 /min to 4.5 ± 1.3/min, P = 0.07) and reduced ELVWI (from 11.0 ± 4.7 ml/kg to 9.0 ± 3.5 ml/kg, P = 0.029). Renal function tests showed that SCr and BUN levels in the CVP↓+ CO↑ group were significantly improved (SCr from 197.1 ± 128.9 mmol/L to 154.4 ± 90.8 mmol/L; BUN from 14.3 μmol/L ± 7.3 to 11.6 ± 7.0 μmol/L, P < 0.05). Conclusions: Lower CVP was associated with increased CO, which may improve the 28-day prognosis in patients with circulatory shock. Notably, higher CO derived from lower CVP may also contribute to renal function improvement.